Analisis Usaha Tani Jagung (Zea Mays) di Desa Kuwolu Kecamatan Bululawang Kabupaten Malang - Sulistiani Sulistiani (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2015)
This article aim to know the effrciency of corn production to achieve the maximal corn product in relation using surface of farmland in which can influences the level of production of corn in Kuwolu village of Kecamatan Bululawang of Kabupaten Malang. Result of analysis of farmer com production in the village of Kuwolu showed that there was a relation between production level of corn with the measure of surface of farmland of famer. The relation be measured with R/C rasio. According to result of analysis of R/C rasio we can understand that the wide surface of farmland of farmer can not improve the level of corn production (Rp. 2.879.114,62 ha-l with R/C rasio 4,00), while narow surface of farmland of farmer could improve the level of corn production (Rp. 3.054.909,12 ha-1 with R/C rasio 3,43). Because on the wide surface of farmland the program of cultivation of corn not done at all of surface of farmland. For the farm of narrow tight agriculture, corn planted at all of its surface. Pursuant to the result of analysis, be suggested to goverment to be can compile the agriculture policy to increase corn production for the narrow farmland and also wide farmland to improve the production of corn further.